2022
DOI: 10.1186/s40001-022-00814-9
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 and TNF-α responses to acute and regular exercise in adult individuals with multiple sclerosis (MS): a systematic review and meta-analysis

Abstract: Background In both the general population and people with multiple sclerosis (PwMS), physical exercise is associated with improved mental well-being. Moreover, there is evidence of the possible protection of physical activity against disease progression in multiple sclerosis (MS). However, the question arises if acute or regular exercise has any impact on the immune system in PwMS. To answer this question, we performed a systematic review and meta-analysis on both plasma and serum cytokine leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 93 publications
0
8
0
Order By: Relevance
“…Moreover, TNF-α disrupted neuronal mitophagy, increased oxidative stress, triggered inflammation, dysregulated GSK-3 β activity, and promoted p-Tau accumulation [ 63 ]. Further, other studies stated that neurodegeneration in patients with T2DM could be considerably lowered by targeting cytokines, cytokine receptors, and nuclear transcription factors linked to inflammation, like IL-6 and TNF- α, alone or in combination [ 48 ]. In this work, pramlintide and liraglutide exhibited anti-inflammatory effects through significantly decreasing the inflammation markers: serum IL-6 and hippocampal TNFα expression when compared to the diabetic group.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TNF-α disrupted neuronal mitophagy, increased oxidative stress, triggered inflammation, dysregulated GSK-3 β activity, and promoted p-Tau accumulation [ 63 ]. Further, other studies stated that neurodegeneration in patients with T2DM could be considerably lowered by targeting cytokines, cytokine receptors, and nuclear transcription factors linked to inflammation, like IL-6 and TNF- α, alone or in combination [ 48 ]. In this work, pramlintide and liraglutide exhibited anti-inflammatory effects through significantly decreasing the inflammation markers: serum IL-6 and hippocampal TNFα expression when compared to the diabetic group.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise may exert immunomodulatory effects in MS [37, 38]. Preventive exercise in experimental autoimmune encephalomyelitis (EAE) has been associated with increased expression of regulatory T cells, reduced activation of peripheral and brain resident immune cells, and decreased production of proinflammatory cytokines [39].…”
Section: Discussionmentioning
confidence: 99%
“…However, whether biological and physiological responses to exercise differ in the context of immune dysregulation is not clear. For example, one meta-analysis found that, in contrast with controls, neither acute nor regular exercise led to a significant change in peripherally circulating IL-6 in pwMS ( 29 ). Moreover, whether the immunomodulatory changes that occur in the context of exercise might have a clinically meaningful impact on the disease course in MS requires specific studies.…”
Section: Exercise Intervention Studies Are Conducted Late In People W...mentioning
confidence: 99%